FASIES AND POROSITY DISTRIBUTION ANALYSIS OF CARBONATE BATURAJA FORMATION IN F FIELD, SOUTH SUMATRA BASIN - Hartono, Aan
Carbonate Baturaja Formation is categorized as primary reservoir in South and Central Sumatra Extension Block, South Sumatra Basin. The failure of several exploration and development wells in the area is generally caused by undeveloped carbonate reservoir due to lateral facies changing or having tight porosity. Research on F Field aims to estimate facies and porosity distribution model of carbonate in the field using seismic facies and seismic multi attributes approach. Results are expected to be used to reduce the failure risk of next well in the F Field and also can become a reference model or analog of carbonate for other fields and exploration prospects with the similar play type. Seismic facies observation in the field shows five facies carbonate that developed in a local isolated platform with southwest-northeast relative trending. Seismic facies map is validated by carbonate facies from well data to obtain the deposition of carbonate facies map in the field. Deposition facies that can be recognized in the research area comprises platform margin, platform interior, platform slope and platform basin. Seismic multi-attribute approach aims to predict artificial logs properties by searching for statistical correlation between properties log data such as porosity, gamma ray, density and acoustic impedance to seismic attributes traces at the well location. The relationships are then applied to 3D seismic data for obtaining pseudo logs properties volume. The results are then extracted on carbonate intervals to get porosity distribution map logs or other properties which have linear relationship to porosity based on well cross plot analysis. Facies and porosity distribution model of carbonate in the research area shows the depositional facies is not the only one factor and the key point which control high porosity distribution. Porosity is more affected by development of secondary porosity as diagenesis processes result which occurred on the upper carbonate interval. Indication of secondary porosity development is shown by presence of vuggy and moldic porosity types from core samples in the F field. Final result of research also recommend to put next infill well location at north or south of F16 well because it shows better reservoir properties compared to others.